Pathology of Trombiculosis caused by Neoschoengastia simonovichi in Wild Red-Legged Partridges (Alectoris rufa). (November 2020) - Molín, Jéssica; Asín, Javier; Stekolnikov, Alexandr A.; de Miguel, Ricardo; Pérez, Marta; Gimeno, Marina; Pinczowski, Pedro; Luján, Lluís
Summary: Lesions caused by trombiculid mite larvae ('chiggers') in birds have been inadequately described. A juvenile red-legged partridge ( Alectoris rufa ) presented with multifocal, crater-like lesions of necrotizing dermatitis, which often contained multiple orange mites. Microscopically, there was a nodular necrotizing and pyogranulomatous dermatitis with occasional intralesional arthropods. Histologically, the mites were readily identified by the presence of stylostomes within the necrotic areas. Morphological and morphometrical studies on isolated mites identified them as Neoschoengastia (Hypogastia) simonovichi . This is the first report of N. simonovichi as an aetiological agent of severe trombiculosis in wild birds in Western Europe. Infestation with this parasite requires further study to understand its role in animal and human trombiculosis and its potential role as a vector of infectious, including zoonotic, agents.